Stream communication between real-time tasks in a high-performance multiprocessor - Leijten, J.A.J.; van Meerbergen, J.L.; Timmer, A.H.; Jess, J.A.G. (Design, automation, and test in Europe : proceedings, February 23-26, 1998, Paris, France, 1998)
The demands in terms of processing performance, communication bandwidth and real-time throughput of many multimedia applications are much higher than today's processing architectures can deliver. The PROPHID heterogeneous multiprocessor architecture template aims to bridge this gap. The template contains a general purpose processor connected to a central bus, as well as several high-performance application domain specific processors. A high-throughput communication network is used to meet the high bandwidth requirements between these processors. In this network multiple time-division-multiplexed data streams are transferred over several parallel physical channels. This paper presents a method for guaranteeing the throughput for hard-real-time streams in such a network. At compile time sufficient bandwidth is assigned to these streams. The assignment can be determined in polynomial time. Remaining bandwidth is assigned to soft-real-time streams at run time. We thus achieve efficient stream communication with guaranteed performance.